Analisis Kebutuhan Bahan Ajar E-Book sebagai Penunjang Pembelajaran Sejarah - Amelia Putri Anggraini; Ridho Bayu Yefterson (Jurusan Sejarah FIS UNP, 2023)
ABSTRACT Teaching materials are materials that have been systematically designed and used by teachers during the learning process. Educational materials used by high school teachers are still conventional, teachers only use educational materials such as textbooks, teaching materials used are monotonous or unvaried and on the teaching material not all can be fully understood by students. The study aims to analyze the need for e-book teaching materials as a support for historical learning in high school for class X students. This research is a phase of the analysis of the ADDIE development model consisting of: student needs analysis, teacher analysis, and curriculum analysis. This research uses data collection techniques such as observations and interviews. The research is carried out in three stages of data analysis, namely data reduction, data presentation, and conclusion drawing. The results obtained in the research analysis of these needs are (1) the analysis of student needs, students need innovative teaching materials (2) teachers need interactive teaching material (3) curriculum analysis, in accordance with the historical learning access that has been achieved with e-book learning materials. The conclusion is that e-book teaching materials are needed as new innovations in the learning process. Keywords: Research and Development, Learning History, E-Book ABSTRAK Bahan ajar merupakan materi yang telah dirancang secara sistematis yang digunakan guru pada saat proses pembelajaran. Bahan ajar yang digunakan guru SMA Negeri 8 Padang masih bersifat konvesional, guru hanya menggunakan bahan ajar berupa buku teks, bahan ajar yang digunakan monoton atau tidak bervariasi dan pada bahan ajar tersebut tidak semua dapat dipahami dengan maksimal oleh peserta didik. Penelitian ini bertujuan untuk analisis kebutuhan bahan ajar e-book sebagai penunjang pembelajaran sejarah di SMA bagi siswa kelas X. Penelitian ini adalah tahap analisis dari model pengembangan ADDIE yang terdiri dari: analisis kebutuhan peserta didik, analisis guru, dan analisis kurikulum. Penelitian ini menggunakan teknik pengumpulan data yaitu observasi dan wawancara. Penelitian ini dilakukan dalam tiga tahap analisis data, yaitu reduksi data, penyajian data, dan penarikan kesimpulan. Hasil yang didapatkan dalam penelitian analisis kebutuhan ini adalah (1) analisis kebutuhan peserta didik, peserta didik membutuhkan bahan ajar yang inovatif (2) Analisis guru, guru membutuhkan bahan ajar yang interaktif (3) analisis kurikulum, sesuai dengan capaian pembelajaran sejarah yang pas dengab bahan ajar e-book. Kesimpulan yang didapat yaitu bahan ajar e-book dibutuhkan sebagai inovasi baru dalam proses pembelajaran. Kata Kunci: Research and Development, Pembelajaran Sejarah, E-Book